Production and Cost of Timber Hauling on Forest Terrain by Manual and Animal Power - Maleta, B. P.; Sood, K. G. (Indian Forester, 1983)
Terrain transport of logs from stump to feeder roads is a strenuous job. In the tropical forests of Central India such movement of timber loads is done by manual carriage and dragging by pair of bullocks. A study has been carried out in Betul Forest in M. P. on cost and production of manual and animal methods of timber transport from Stump to feeder roads. The lead for off-road transportation of logs and poles over undulating and bouldary terrains was upto 100 metres to tbe feeder roads. The regressions for time over load volume and lead distance have been derived. The log volume in each single load influences the production efficiency to greater extent than the transport lead. Engagement of pair of bullocks for skidding timber loads over distances 20 m to 100 m is more economical than manual carriage and can further be improved by improvisation suggested in this paper.